Clinical Application of Circulating Tumor Cells in Gastric Cancer - Moon Won Lee; Gwang Ha Kim; Hye Kyung Jeon; Su Jin Park (Gut and Liver, 2019)
Early detection and accurate monitoring of cancer is important for improving clinical outcomes. Endoscopic biopsy and/or surgical resection specimens are the gold standard for diagnosing gastric cancer and are also useful for selecting therapeutic strategies based on the analysis of genomic/immune parameters. However, these approaches cannot be easily performed because of their invasiveness and because these specimens do not always reflect tumor dynamics and drug sensitivities during therapeutic processes, especially chemotherapy. Accordingly, many researchers have tried to develop noninvasive novel biomarkers that can monitor real-time tumor dynamics for early diagnosis, prognostic evaluation, and prediction of recurrence and therapeutic efficacy. Circulating tumor cells (CTCs) are metastatic cells that are released from the primary tumors into the blood stream and comprise a crucial step in hematogenous metastasis. CTCs, as a liquid biopsy, have received a considerable amount of attention from researchers since they are easily accessible in peripheral blood, avoiding the invasiveness associated with traditional biopsy techniques; they can also be used to derive clinical information for monitoring disease status. In this review, with respect to CTCs, we summarize the metastatic cascade, detection methods, clinical applications, and prospects for patients with gastric cancer.